Plant functional constraints guide macroevolutionary trade‐offs in competitive and conservative growth responses to nitrogen. (7th March 2016) - Wooliver, Rachel; Pfennigwerth, Alix A.; Bailey, Joseph K.; Schweitzer, Jennifer A.
Summary: Decades of research show that plants vary in their growth responses to increasing soil nitrogen (N), supporting theory on evolutionary trade‐offs between competitive and conservative growth strategies. However, we lack an explicit examination of the evolutionary processes guiding trade‐offs in competitive and conservative growth responses to N addition (GRN), processes which should include selection across environmental gradients and constraint within certain plant functional types. To determine current variation in GRN across plants, we collected previously published data on total biomass responses of 125 terrestrial plant species to N fertilization, relative to control soil N conditions. We calculated phylogenetic signal of GRN to assess the influence of shared evolutionary history on variation in N use capacities. To determine whether this variation is consistent with stabilizing selection towards unique N use capacities across environmental gradients and plant functional types, we compared the fit (second‐order Akaike Information Criterion) of species' GRN data to models that approximate evolution according to genetic drift with and without stabilizing selection across plant functional types, biomes, latitude, mean annual temperature and annual precipitation. More than one in four species in our analysis responded negatively or neutrally to increasing soil N and responses ranged from a 60% decrease to an 1800% increase in biomass with added N. We identified a significant phylogenetic signal for GRN, and evolutionary models incorporating stabilizing selection plus genetic drift explained more variation in GRN than models incorporating genetic drift alone. Parameter estimates from selection‐based models indicate that plant functional types have experienced selection towards GRN values (i.e. evolutionary optima) that differ more than among biomes or across climatic gradients. Overall, our results suggest that phylogenetic relatedness and stabilizing selection associated with functional constraints are two aspects of past evolution that govern whether species will be winners or losers in global soil N addition scenarios. Abstract : Lay Summary